EDUCATING THE PUBLIC ABOUT THE HEALTH BENEFITS OF KALAMANSI ORANGES AT ARFAN JAYA PHARMACY - Haque , Aina Fatkhil; Dian Handayani; Aisyah Putri Hasanah; Indry Lestya; Nur Afifah; Rosalina Evelin; Elkharis Eirene Lamtiar Sirait; Nadia Fransiska; Puput Ajeng Karlina; Fhagel Iriansyah (Jurnal Pengabdian, 2025)
A community education activity on the health benefits of calamansi (Citrus microcarpa) was conducted at Arfan Jaya Pharmacy as part of a promotive and preventive effort to raise public awareness of the importance of consuming natural, nutrient-rich ingredients. Calamansi is known to be rich in vitamin C and antioxidants, with potential benefits as an immune booster and detoxifying agent. This educational initiative aimed to deliver scientifically accurate yet easily understandable information to the general public, promote healthy lifestyle habits, and reinforce the role of pharmacies as accessible health information centers. The method of delivery included direct counseling, leaflet distribution, and interactive discussions with participants. The results indicated an increase in public knowledge about the benefits of calamansi and a growing interest in incorporating it into daily consumption. It is hoped that similar activities can be conducted regularly to broaden their positive impact on public health.